Heterologous Prime-boost COVID-19 Vaccination - Vishal R. Tandon; Annil Mahajan (Dr. Annil Mahajan, 2021)
There is a significant recent international interest in heterologous prime-boost COVID-19 vaccination. It may prove useful in avoiding the supply shocks or shortages that might otherwise reduce the speed of vaccine roll-out in any country including India. Additionally, several countries are now advising that individuals previously primed with this vaccine should now receive an alternative vaccine as their second dose, most commonly mRNA vaccines administered in a heterologous prime-boost schedule. The proposed benefits of heterologous vaccination implementation are 100% seroconversion, greater efficacy and enhanced safety as well as tolerability then the homologous vaccination programme currently being operational worldwide. Further, it is also hypothesized that such heterologous vaccination may also prove very effective in combating emerging COVID variants including recent delta and delta plus variant.